2016
DOI: 10.1002/adhm.201600236
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Nerve Regeneration: Current Status and New Strategies Using Polymeric Materials

Abstract: Experiments concerning peripheral nerve regeneration have been reported since the end of the 19th century. The need to implement an effective surgical procedure in terms of functional recovery has resulted in the appearance of several approaches to solve this problem. Nerve autograft was the first approach studied and is still considered the gold standard. Since autografts require donor harvesting, other strategies involving the use of natural materials have also been studied. Nevertheless, the results were no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 131 publications
(167 reference statements)
2
88
0
Order By: Relevance
“…5,8,9 As an alternative, most of the current research efforts are directed toward the development of nerve guidance conduits (NGCs) from natural or synthetic polymers. 1012 An NGC is supposed to maintain the nerve regeneration environment, guide axon regeneration, keep the nerve growth factors (NGFs) in the wound healing space, and prevent the invasion of cells that could form scars. 1214 Among the reported systems, NGCs based on electrospun fibers have received the most attention owing to their highly porous walls and their ability to present the fibers as a uniaxially aligned array.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,8,9 As an alternative, most of the current research efforts are directed toward the development of nerve guidance conduits (NGCs) from natural or synthetic polymers. 1012 An NGC is supposed to maintain the nerve regeneration environment, guide axon regeneration, keep the nerve growth factors (NGFs) in the wound healing space, and prevent the invasion of cells that could form scars. 1214 Among the reported systems, NGCs based on electrospun fibers have received the most attention owing to their highly porous walls and their ability to present the fibers as a uniaxially aligned array.…”
Section: Introductionmentioning
confidence: 99%
“…1012 An NGC is supposed to maintain the nerve regeneration environment, guide axon regeneration, keep the nerve growth factors (NGFs) in the wound healing space, and prevent the invasion of cells that could form scars. 1214 Among the reported systems, NGCs based on electrospun fibers have received the most attention owing to their highly porous walls and their ability to present the fibers as a uniaxially aligned array. 15 The aligned fibers can provide a topographical cue to direct and enhance axonal extension during regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many natural and synthetic polymers with interesting properties can be incorporated into SF as reinforcement . On the benefit of these advantages, SF‐based biomaterials have become increasing popular in the field of peripheral nerve regeneration . Our previous study showed that SF/P(LLA‐CL) nerve conduits promote nerve regeneration more effectively than P(LLA‐CL) conduits .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, nerve conduits made of synthetic or natural polymers have become a promising alternative to autologous nerve grafts. A number of nerve conduits have shown to successfully bridge peripheral nerve gaps and support nerve regeneration …”
Section: Introductionmentioning
confidence: 99%
“…Peripheral nerve injury is a common disease across the world, which can be caused by traffic accidents, work accidents, natural disasters, warfare, tumor damage, etc . Nerve scaffolds are often used to bridge large nerve defects.…”
Section: Introductionmentioning
confidence: 99%